Chaines de reformulation dans un corpus de production-traduction. Les influences du déjà-dit dans des écritures-réécritures traductionnelles - Leblay Christophe; Leblay Tarja (France, 2022)
This study sheds light on the phenomenon of reformulating in a corpus of writing and translation process from a genetic criticism perspective. In this study, the already-there is then doubly present: a first time, in the form of the source text, given in Finnish, and a second time, in the form of a proposition discussed in French, by the students and the teacher. The idea was to introduce already-said and already-written in order to be able to measure its impact on the rewritings-translations. In this work, we will endeavor to highlight certain phenomena of reformulation (new writings referred to earlier writings), pointing precisely to the chains of occurrences present in the two rewritings-translations.